Mobilidade no espaço de vida em idosos com doença de Alzheimer - Langelli, Tamiris de Cássia Oliva (2021)
Introduction: Mobility is an important component of functioning. Motor and cognitive impairment in older people with Alzheimer’s disease (AD) can exert a negative impact on life-space mobility (LSM). Objective: Compare LSM in older people with mild to moderate AD and those with preserved cognition and determine associations with functioning, physical activity level, depressive symptoms, physical performance of the lower limbs, and cognitive functions. Methods: LSM was assessed using the Life Space Assessment in 24 older people with preserved cognition (PreCog) and 33 with AD. The following instruments were also applied: World Health Organization Disability Assessment Schedule (WHODAS 2.0), Addenbrooke’s Cognitive Examination – revised version (ACE-R), Geriatric Depression Scale (GDS-15), Modified Baecke Questionnaire for Older Adults (MBQOA), and Short Physical Performance Battery (SPPB). Statistical analysis involved the unpaired t-test or Mann-Whitney test for comparisons between groups and Spearman’s correlation test. Results: The AD group had a lower total LSM score compared to the PreCog group (44 vs. 64 [U = 120.500; p < 0.01); 21% of the AD group were restricted to their homes when no assistance was available. In both groups, moderate correlations were found between LSM and both functioning and physical activity level. A moderate correlation with depressive symptoms was also found in the PreCog group. Conclusion: Older adults with mild to moderate AD have lower LSM and require assistance to achieve higher levels of mobility. Only functioning and physical activity level were correlated with LSM in older people with AD, suggesting that broader interventions beyond merely physical and cognitive aspects should be explored.